Characterizing behavioral health-related emergency department utilization among children with Medicaid: Comparing high and low frequency utilizers. (14th September 2019) - Lynch, Sean; Pines, Jesse; Mutter, Ryan; Teich, Judith L.; Hendry, Phyllis
ABSTRACT: While the frequency of children's behavioral health (BH)-related visits to the emergency department (ED) is rising nationwide, few studies have examined predictors of high rates of ED use. This study examines Florida Medicaid claims (2011–2012) for children age 0–18 who were seen in an emergency department (ED) for behavioral health (BH) conditions. A logistic regression model was used to explore factors associated with frequent ED use and patterns of psychotropic medication utilization. The majority (95%) of patients with at least one BH-related ED visit had three or fewer of these visits, but 5% had four or more. Seventy-four percent of ED visits were not associated with psychotropic medication, including over half (54%) of visits for attention deficit hyperactivity disorder (ADHD). Frequent ED use was higher among older children and those with substance use disorders. The implementation of interventions that reduce non-emergent ED visits through the provision of care coordination, social work services, and/or the use of community health workers as care navigators may address these findings.